STUDI KOMPARATIF KERUSAKAN BETON PADA STRUKTUR KOLOM YANG KEROPOS DENGAN METODE GROUTING - Hariati Pratiwi; Yayuk Setyaning Astutik; Usmanul Hayadi Umar (Program Studi Sarjana Teknik Sipil Universitas Internasional Batam, 2020)
Concrete is a material widely used in construction projects. The quality of concrete is strongly influenced by some of its constituent materials such as water, cement, coarse aggregates, fine aggregates and other additives. In the implementation of construction using concrete, there is a great deal of damage to concrete materials, one of which is porous or with other names voids (cavities or holes). Therefore, repair methods used for occurring damage in concrete are needed. This study used a 15cmx15cmx15cm cube-shaped concrete sample divided into three samples, namely 6 cubes of normal concrete, 6 cubes of concrete made intentionally porous with grouting method using Sikagrout215, and concrete which was intentionally made porous with a method of grouting using a mixture of cement and water (cement paste) 6 cubes. Each cube were tested its compressive strength at the stage of 7, 21 and 28 days. The results showed that the cause of porous concrete was caused by several factors including cement water factor, lack of compaction process, the aggregate ratio used, and poor workability. Concrete compressive strength results at 28 days showed that the compressive strength of normal concrete was 230,459 kg / cm², concrete grouting with 215 cycles of 318,532 kg / cm², and grouting concrete with a mixture of cement and water 316,707 kg / cm². Grouting concrete using 215 cycles has the largest value among the three samples. Hence, in this study the grouting method is the right choice to make porous concrete repaired. Keywords: porous concrete, grouting, concrete compressive strength, column, structure